2020
DOI: 10.9755/ejfa.2020.v32.i11.2197
|View full text |Cite
|
Sign up to set email alerts
|

The peel essential oil composition of bergamot fruit (Citrus bergamia, Risso) of Reggio Calabria (Italy): a review.

Abstract: Bergamot (Citrus bergamia, Risso) grows exclusively in the province of Reggio Calabria (Southern Italy). Most part of this territory lies on by the Ionian or the Tyrrhenian sea, with over 700 kilometers of coastline, it has one of the highest values of heliophany in Italy and it is protected, from the Northern winds, by the Aspromonte mountain massif. Most part of the bergamot cultivation area is located between Scilla (West) and Monasterace (East) in a coastal strip with a width up to 12 km from the coast. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
(52 reference statements)
1
26
1
Order By: Relevance
“…It is well known that differences in the composition of EOs and organic extract depend on the species [7], the phenological stage [9], agroecological conditions [6,8,16,17], pretreatment [11,14], processing conditions [6,[10][11][12][13][14]18], and extraction method [10][11][12][13][14]. Table 2 summarizes the impact of the different extraction methods and conditions on the concentration of the main volatile compounds in cloves.…”
Section: Effect Of the Extraction Methods On The Concentration Of The Main Volatile Compounds Of The Essential Oil And Organic Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that differences in the composition of EOs and organic extract depend on the species [7], the phenological stage [9], agroecological conditions [6,8,16,17], pretreatment [11,14], processing conditions [6,[10][11][12][13][14]18], and extraction method [10][11][12][13][14]. Table 2 summarizes the impact of the different extraction methods and conditions on the concentration of the main volatile compounds in cloves.…”
Section: Effect Of the Extraction Methods On The Concentration Of The Main Volatile Compounds Of The Essential Oil And Organic Extractmentioning
confidence: 99%
“…Various authors have reported that the composition and extracted yield of EOs depends on the species, soil composition, plant organ (aerial parts, inflorescence, or roots), age, cycle stage, selected extraction method, and conditions of extraction [2,[5][6][7][8][9][10][11][12][13][14][15][16][17]. Mohamed et al [16] reported that the application of different fertilizers (organic or chemical fertilizers) influences not only the growth or productivity of the plant but also the final composition and yield of the EO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24], Coriandrum sativum L. [25], Mentha piperita L. [26], Cannabis sativa L. [27] and Boletus edulis [28]. Especially interesting was high content of (E)-α-bergamotene, which is characteristic for Citrus bergamia Risso fruit [29] and pyridine, which was reported in similar amounts in Cicer arietinum L. [30].…”
Section: Discussionmentioning
confidence: 86%
“…Twenty-two major volatile compounds were selected for multivariate statistical analysis, among which d-limonene was the highest relative content (Table S5) and the most abundant ingredient in other citrus peel, such as bergamot (Citrus bergamia (Rutaceae)), lemon (Citrus limon (Rutaceae)), and grapefruit (C. paradisi (Rutaceae)). (Gioffrè et al, 2020;Miya et al, 2021;Verzera et al, 2001). The reported literature has illustrated that the γ-terpinene is lower in grapefruit peel (about 0.1%), but it is higher in the oriental mandarin cultivars peel (Owari and Okitsu), ranging from 3.6% to 4.1% (Merle et al, 2004).…”
Section: Multivariate Statistical Analysis Of Main Volatile Compounds In Crcp During Storagementioning
confidence: 98%